2008
DOI: 10.1634/stemcells.2008-0010
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Stem Cell-Derived Neurons as a Cellular System to Study Gene Function: Lack of Amyloid Precursor Proteins APP and APLP2 Leads to Defective Synaptic Transmission

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 65 publications
1
35
0
Order By: Relevance
“…APP is a long-chain transmembrane protein, whose precise physiological function is not yet fully understood. Recent data strongly support a role for APP in embryonic neural organogenesis [19] , neurite outgrowth [20] and synaptogenesis [21] . Moreover, using proteomic and bioinformatic tools revealed that APP might interact with more than 30 proteins, suggesting that many physiological processes might be affected [22] .…”
Section: Ap Characteristicsmentioning
confidence: 87%
“…APP is a long-chain transmembrane protein, whose precise physiological function is not yet fully understood. Recent data strongly support a role for APP in embryonic neural organogenesis [19] , neurite outgrowth [20] and synaptogenesis [21] . Moreover, using proteomic and bioinformatic tools revealed that APP might interact with more than 30 proteins, suggesting that many physiological processes might be affected [22] .…”
Section: Ap Characteristicsmentioning
confidence: 87%
“…It has been demonstrated that AICD possesses transactivation activity in luciferase assays (Cao and Sudhof, 2001), controls the expression of endogenous target genes (Alves da Costa et al, 2006;Baek et al, 2002;Belyaev et al, 2009;Liu et al, 2007;Muller et al, 2006;Pardossi-Piquard et al, 2005;Schrenk-Siemens et al, 2008;von Rotz et al, 2004;Zhang et al, 2007) and, together with Fe65 and Tip60, localizes to spherical nuclear complexes that are thought to represent sites of transcription (Konietzko et al, 2008;von Rotz et al, 2004). AICD can be generated from APP by two different proteolytic processing pathways and we have analyzed their differential nuclear signaling capacity.…”
Section: Discussionmentioning
confidence: 99%
“…However, organotypic hippocampal slice cultures can be studied in case of early postnatal lethality. Of note, using this technique, APP/APLP2-DKO mutants revealed defects in basal glutamatergic synaptic transmission that were absent in single mutants (Schrenk-Siemens et al 2008). Thus, a more complete picture of APP/APLP function in the CNS will await the generation of brain specific conditional mutants.…”
Section: Combined Knockouts Of App Family Membersmentioning
confidence: 99%